The portfolio organizer : succeeding with portfolios in your classroom - Rolheiser-Bennett, Noreen Carol (Association for Supervision and Curriculum Development, 2000)
The Portfolio Organizer stands out as a superb contribution to the vital field of accountability for learning. This book is distinguished by the presence and integration of a conceptual framework and a superb array of practical examples. Nearly every key issue is anticipated and addressed in this accessible and clear treatment of a complex topic. The reason that this book is so good is that the authors have been immersed in pioneering work on portfolios for a decade. They have developed their ideas through work with their own students, and through a wide range of research and evaluation projects including new initiatives involving elementary and secondary school students, initial preparation of teachers, and continuous professional development of teachers and administrators. They have learned by grappling with the complex issues of introducing evaluation that simultaneously serves improvement and accountability goals. The result is a great practical book that can help educators develop their understanding and use of portfolios as a route to reform. This book provides educators with a flexible framework to guide decision making for effective and efficient use of portfolios in classrooms and schools. It is designed to assist classroom teachers, administrators, staff developers, and university professors in identifying, organizing, and acting upon the many challenges and possibilities inherent in portfolio implementation. Specifically, The Portfolio Organizer targets the major categories of decision making and assists teachers in making decisions about effective portfolio implementation in classrooms. In addition, the book addresses professional portfolios and can be used by educators to develop and maintain their own portfolios.-(From the Foreword by Michael Fullan).